AnchoisFert: A New Organic Fertilizer from Fish Processing Waste for Sustainable Agriculture. Issue 5 (2nd March 2022) - Muscolo, Adele; Mauriello, Francesco; Marra, Federica; Calabrò, Paolo Salvatore; Russo, Mariateresa; Ciriminna, Rosaria; Pagliaro, Mario
Abstract: The "AnchoisFert", the solid residue comprised of milled anchovy leftovers after fish oil extraction with biobased limonene, is a powerful organic fertilizer. Employed to promote the growth of Tropea's red onion ( Allium cepa ), the fertilizer turns out to largely be superior to commonly used organic (manure) and chemical (nitrogen phosphorous potassium) fertilizers. Rich in proteins, organic carbon, flavonoids, magnesium, potassium, phosphate and sulfate, and devoid of antibiotics and antibiotic resistance genes, the new organic fertilizer can replace both conventional organic and inorganic fertilizers. This discovery closes the fishing material cycle for the most fished species across the seas opening the route to a new class of organic fertilizers of exceptional performance derived from abundant biowaste via a low‐cost and environmentally‐friendly circular economy process. Abstract : The "AnchoisFert", the solid residue comprised of milled anchovy leftovers after fish oil extraction with biobased limonene, is shown to be a powerful organic fertilizer, rich in proteins, organic carbon, flavonoids, magnesium, potassium, phosphate, and sulfate. This discovery closes the fishing material cycle for the most fished species across the seas.